Weltpunkt Wien : Un regard sur Vienne: 1985 - Fleck, Robert; Bonk, Ecke; Draxler, Helmut; Carrefour de la Création contemporaine, Strasbourg (Wien - München : LV - Löcker Verlag, 1985)
Lassnig, Maria ; Rainer, Arnulf ; Nitsch, Hermann ; Brus, Günter ; Muehl, Otto ; Oberhuber, Oswald ; Gironcoli, Bruno ; West, Franz ; Schmalix, Hubert ; Anzinger, Siegfried ; Caramelle, Ernst ; Rockenschaub, Gerwald ; Brandl, Herbert ; Kowanz, Brigitte ; Graf, Franz ; Walde, Martin ; Kogler, Peter ; etc.
Weltpunkt Wien : Un regard sur Vienne: 1985, Pavilion Josephine, Strassbourg, 20. Juni bis 14. Juli 1985
Duits
kunstcatalogus
Keywords: Oostenrijk; Wenen